Mechanical properties and bruise susceptibility of tomatoes related to impact direction and drop-height - Aktas, Turkan (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2008)
The study evaluated the mechanical properties and bruise susceptibility of tomatoes (Enda F1 cultivar). Compression tests were carried out at 1 mm min -1 load velocity to determine mechanical properties (deformation, bioyield point force, deformation energy and Poisson's ratio). Impact tests were conducted using a pendulum with 50 cm arm length to determine the absorbed energy, bruise volume and bruise susceptibility. Impact tests were carried out at two positions of the tomato, namely impact from the under side and cheek side at four drop heights (20, 30, 40 and 50 cm) to determine different impact energy levels. In addition, dimensional properties such as length, width and mass were also measured. More deformation occurred in the tomato if force was applied to the cheek side, compared with deformation in the flower-stalk side. Average deformation energy was found to be 148.5 Nmm when compression was applied to the flower-stalk side and 98.33 Nmm when applied to the cheek side. Mean Poisson's ratio was calculated as 0.388. The maximum absorbed energy was found to be 611 Nmm for the cheek side at 50 cm drop height while the minimum value was determined as 209.8 Nmm for the underside at a drop height of 20 cm.